(3SbhW ZQfGWIs - (3GdeYdha, ahRjs; (3CHh GdYWG, CSeGAs; (3efjQ, TjeGAs ((3GdbGgQIs (3EHOGY ddfTQ hGdJhRjYs, 2024)
(3jMcj GdYed MGdI GdhVY GdOGNdj deOjfI GdCfOdS, hGdPj jHQR bUI SbhW gPg GdeOjfI HGdJaUjd, hcja Cf GdMcGe hGdQYjI aj gPg GdaJQI cGfhG eTZhdjf HCfaSge CcKQ ef TZdge HCehQ GdeOjfI, aHjfeG cGf jba GdCSHGf Ydi CHhGH GdeOjfI jObhf WHhd GdMQH, cGf GdMGce aj GdhbJ PGJg aj UQGY eY CMO QYjJg ef CLd GeQCI, hjOHQ dcd efgeG GdecGFO hGdceGFf, jMcj GdeDda Pdc aj CSdhH MjGOj hehVhYj, MJi SbhW gPg GdeOjfI hcja de jab Gdedc ef ZahJg EdG HYO Cf VGY cd TF habO GdeSdehf ZUfge GdQWjHs
Keywords: (3GdeSQMjGJ GdYQHjIs -- (3eUQs; (3GdeSQMjGJ GdeUQjIs